Transportation Technology in a Duopoly Model of International Trade - Andrea Mantovani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2001)
In this paper I will evaluate the role of R&D investment in transport and communication in a duopoly with trade. I will in fact consider the strategic behavior of two firms located in two different countries. They can activate R&D investments in order to improve the technology of the transportation process. Transport and communication (TC) costs are of iceberg type, i.e. only a fraction of the goods shipped abroad reaches the foreign market. I will then study a game in which firms may priorly commit themselves to a certain level of R&D investment and then they play in the market. As for the marketgame, I will consider both a Cournot duopoly with homogeneous products and a Bertrand duopoly with differentiated goods. In both models, my analysis suggests that firms are willing to invest in transport and communication technology when such a strategy yurns out to be efficient, i.e. when it does not imply an excessive cost. More precisely, a variety of equilibria will aarise as a result of different levels of TC r&D efficiency. If the cost is low the game has an equilibrium in dominant strategies where both firms invest in TC and maximize the aggregate profit. As the cost increases, the game becomes a prisoner`s dilemma; both firms still invest in Tc but they do not reach the Pareto-efficient solution. For even higher levels of the cost required, the game shows an equilibrium in dominant strategies where no firms finances TC R&D and the aggregate profit is maximized.
Keywords: 330